P179 Utilisation of respiratory and haematology multi-disciplinary team (mdt) meeting for effective follow-up and management of pulmonary embolism (pe) in a district general hospital. (15th November 2017) - McAuley, H; Brij, SO; Calvert, LD
Abstract : Background: Patients are diagnosed with PE in our hospital by a variety of health care practitioners in numerous clinical settings including Ambulatory Care. Following diagnosis and initiation of therapy, all patients should be referred to the PE Clinic for follow-up at 3 months to ensure that risk stratification for on-going venous thrombotic episode (VTE) is undertaken, anti-coagulation therapy duration is optimised and adequate screening for cancer and chronic thrombo-embolic pulmonary hypertension (CTEPH) undertaken. Aim: To evaluate the effectiveness of PE MDT (Respiratory and Haematology) meeting prior to Respiratory-led PE follow-up Clinic. Methods: PE patients referred to the PE MDT from January 2016–2017 were included. Demographic data was collected (gender, age, co-morbidities, referral source). The cause of VTE was established and duration of anti-coagulation therapy reviewed. Risk stratification and screening for cancer and PHT outcomes were documented. Results: 113 patients (56 male [49.5%]; average age 64 years; range 20–96) were discussed. 51 (45%) presented via Ambulatory Care with only 9 (8%) from Respiratory. PE was idiopathic in 56 (49.5%) of which 14 (25%) were a second VTE. Secondary causes included surgery (24) and BMI ≥40 (11). 66 (58%) received screening tests to exclude underlying cancer: new cancer diagnosed in 2 (lung, urological); 2 had cancer recurrence within 1 year; 5 required lung nodule surveillance. All patients were screened with echocardiography and only 3 did not undertake 6 min walk test (immobility). Subsequently, 2 patients required referral for further investigation of CTEPH. Haematology advice changed management in 47 (42%) cases, usually increased duration of anti-coagulation therapy. 4 patients had high DASH (D-Dimer, Age, Sex, Hormones) score post-treatment necessitating anti-coagulation re-start. 1 patient had early PE recurrence following completion of recommended duration anti-coagulation. Only 7 patients required on-going Haematology referral and investigation. Respiratory advice changed treatment in 3 persons by reducing recommended duration of therapy. 16 patients required on-going Respiratory review for another respiratory illness. Conclusion: A systematic MDT approach has been shown to be safe and effective and optimises PE patient care. The next step would be to have Respiratory and Haematology input at MDT with an Acute Physician–led PE follow–up Clinic.